Impact of Gender Differences in the Prevalence of Food Security among Rural Households in Kenya - Njoroge, Jacqeline; Murunga, James; Karau, James (East African Journal of Business and Economics, 2024)
Gender inequality in access to productive and economic resources has been a significant issue in sub-Saharan Africa, particularly in Kenya, where rural households face varying levels of food security. While existing research has extensively examined the general determinants of food security among rural households in Kenya, there is a significant gap in understanding how these determinants differ by gender. Utilizing Kenya Intergrated Household Budget Survey (KIHBS) 2015/16 data and a binary logistic regression model, the study seeks to examine the impact of gender differences on the prevalence of food security among rural households in Kenya, while controlling for a set of household demographic and socio-economic characteristics. The findings revealed significant gender disparities, with female-headed households exhibiting higher food security scores compared to male-headed households. This is attributed to women’s greater involvement in household food management and decision-making processes. The findings further revealed that the education status of the household head and household size are important determinants of food security among female-headed households while the education status of the household head, household size, access to credit and income are important determinants of food security among male-headed households. Given the findings of the study, it is evident that gender differences significantly influence food security among rural households in Kenya. The study therefore recommends that policy makers should incorporate gender-specific considerations into the design of food security policies and reforms.
Keywords: Gender, Food Security, Male Headed Households, Female Headed Households, Kenya